2014
DOI: 10.1080/09540121.2014.987105
|View full text |Cite
|
Sign up to set email alerts
|

Optimism, community attachment and serostatus disclosure among HIV-positive men who have sex with men

Abstract: This study investigated the relationship between HIV health optimism (HHO) (the belief that health will remain good after HIV infection due to treatment efficacy), HIV-positive community attachment (HCA), gay community attachment (GCA) and serostatus disclosure to casual sex partners by HIV-positive men who have sex with men (MSM). Cross-sectional questionnaire data were gathered from 97 HIV-positive MSM attending an HIV treatment clinic in Dublin, Ireland. Based on self-reported disclosure to casual partners,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…In a baseline assessment of an randomised controlled trial evaluating efficacy of a safer sex intervention, 31% of 138 GBMSM who reported having sex in the past six months "disclosed to less than 100% of all sex partners" (Przybyla et al, 2012) Among 991 young GBMSM ( < 25 years) attending for HIV care, 53.1% "did not disclose to a current sex/romantic partner who was not a boyfriend" (Cook et al, 2015) Among 250 MSM enrolled in a disclosure intervention, 28% of sexual encounters involved the participant "not disclosing at or before the specific sexual encounter" (Serovich et al, 2018). Evidence from the UK remains limited, with a cross-sectional questionnaire study of HIV-outpatients in Dublin's largest HIV clinic (2012) reporting that 34% of 97 GBMSM "never disclosed to any of their casual partners in the last 6 months" (Murphy, Hevey, O'Dea, Ní Rathaille, & Mulcahy, 2015). In our study, 44% of GBMSM were classified as having lower sexual disclosure, a proxy for non-disclosure to new sex partners.…”
Section: Discussionmentioning
confidence: 99%
“…In a baseline assessment of an randomised controlled trial evaluating efficacy of a safer sex intervention, 31% of 138 GBMSM who reported having sex in the past six months "disclosed to less than 100% of all sex partners" (Przybyla et al, 2012) Among 991 young GBMSM ( < 25 years) attending for HIV care, 53.1% "did not disclose to a current sex/romantic partner who was not a boyfriend" (Cook et al, 2015) Among 250 MSM enrolled in a disclosure intervention, 28% of sexual encounters involved the participant "not disclosing at or before the specific sexual encounter" (Serovich et al, 2018). Evidence from the UK remains limited, with a cross-sectional questionnaire study of HIV-outpatients in Dublin's largest HIV clinic (2012) reporting that 34% of 97 GBMSM "never disclosed to any of their casual partners in the last 6 months" (Murphy, Hevey, O'Dea, Ní Rathaille, & Mulcahy, 2015). In our study, 44% of GBMSM were classified as having lower sexual disclosure, a proxy for non-disclosure to new sex partners.…”
Section: Discussionmentioning
confidence: 99%
“…Participants attended a large infectious diseases clinic in Dublin, Ireland. All had taken part in a previous quantitative study, and as part of that study had indicated a willingness to be interviewed, and provided written informed consent (Murphy, Hevey, O’Dea, Ní Rathaille, & Mulcahy, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini dikarenakan adanya rasa optimis yang besar sehingga menghalangi suatu individu dalam memahami manfaat dari suatu pengungkapan status HIV, sehingga ODHA tersebut merasa baik-baik saja dan tidak perlu untuk mengungkapkan status HIV-nya. Komunitas yang juga memiliki status HIV positif yang sama dengan status berorientasi seksual yang sama juga dapat memfasilitasi gay dalam menentang efek negatif dari perilaku pengungkapannya (Murphy et al, 2015). Adanya dukungan sebaya diantara pasangan yang berorientasi seksual gay memiliki hubungan yang begitu signifikan terhadap keterbukaan status HIV mereka (Fitriyani & Waluyo, 2019).…”
Section: Padaunclassified